Sharī‘ah-Based Governance as a Contextual Normative Framework: Relevance and Reconstruction in Modern State Governance - Muhammad Abu Dzar; Muhammad Azizzullah Ilyas; Ifansyah Putra; Essa Lafi Hassan Al Smadi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
This article reconceptualizes Siyāsah Syar‘iyyah as a dynamic normative-epistemological framework in contemporary state governance. Despite the growing body of literature on Islamic governance, prior studies have largely remained at the descriptive or compatibility level, without offering a systematic methodological reconstruction capable of bridging classical jurisprudence and modern political realities. Addressing this gap, this study repositions Siyāsah Syar‘iyyah as an ijtihād-based model grounded in maqāṣid al-sharī‘ah, with an emphasis on public interest (al-maṣlaḥah al-mu‘tabarah), justice (taḥqīq al-‘adl), prevention of harm (raf‘ al-mafsadah), and consideration of long-term consequences (i‘tibār al-ma‘ālāt). Using a normative-doctrinal qualitative approach, this research examines the jurisprudential thought of al-Māwardī, al-Qarāfī, and Ibn al-Qayyim alongside contemporary debates on law and the state. This study argues that governance belongs to the domain of revisable norms (aḥkām mutaghayyirah), so that institutional forms such as constitutionalism and democracy can be understood as evaluative instruments, not fixed Islamic models. The findings indicate that Siyāsah Syar‘iyyah is compatible with modern political systems — including democracy and constitutionalism — as long as they are oriented toward justice and the public good, since such systems function as evaluative instruments (wasā‘il), not fixed Islamic models. The contribution of this research lies in the reconstruction of Siyāsah Syar‘iyyah as a contextual, maqāṣid-based, and outcome-oriented normative framework, operationalized through three strategic mechanisms: (1) the institutionalization of collective ijtihād in governance; (2) maqāṣid-grounded legislation; and (3) the operationalization of Islamic political ethics in public administration. In the Indonesian context, this framework demonstrates that Islamic governance values can be substantively embedded within constitutional practice, religious court jurisprudence, and sharia-based legislation — such as the KHI, KHES, and regulations on zakat and waqf — without necessitating a formal Islamic state